(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
The article highlights the issue of cataloging and publishing the works of A. Urinboev in his scientific activities, analyzes the scientist’s contribution to the cataloging of manuscripts stored at the Institute of Oriental Studies of the UzSC.